Рейтинг

Оцените: 100% - 1 голосов

100%

алгебра 7 класс

Номер 778

Условие:

Упростите:
а) (а2 - 7)(а + 2) - (2а - 1)(а - 14);
б) (2 - b)(1 + 2b) + (1 + b)(b3 - 3b);
в) 2x2 - (х - 2y)(2x + у);
г) (m - 3n)(m + 2n) - m(m - n);
д) (а - 2b)(b + 4а) - 7b(а + b);
е) (р - q)(p + 3q) - (p2 + 3q2).

 

Ответ:

а) (а2 - 7)(а + 2) - (2а - 1)(а - 14) = a + 2а2 - 7a - 14 - 2а2 + 28a + a - 14 = a3 + 22a - 28;
б) (2 - b)(1 + 2b) + (1 + b)(b3 - 3b) = 2 + 4b - b - 2b2 + b3 - 3b + b4 - 3b2 = b4 + b3 - 5b2 + 2;
в) 2x2 - (х - 2y)(2x + у) = 2x2 - 2x2 - ху + 4ху + 2y2 = 2y2 + 3хy;
г) (m - 3n)(m + 2n) - m • (m - n) = m2 + 2mn - 3mn - 6n2 - m2 + mn = -6n2;
д) (а - 2b)(b + 4а) - 7b • (а + b) = аb + 4а2 - 2b2 - 8аb - 7аb - 7b2 = 4а2 - 14аb - 9b2;
е) (р - q)(p + 3q) - (p2 + 3q2) = p2 + 3pq - рq - 3q2 - p2 - 3q2 = 2рq - 6q2.